2017
DOI: 10.1080/03007995.2017.1354832
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of tadalafil in pediatric patients with pulmonary arterial hypertension: a sub-group analysis based on Japan post-marketing surveillance

Abstract: This manuscript reveals the use of tadalafil in the real-world pediatric population with an acceptable safety profile in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Yamazaki et al investigated the efficacy of tadalafil in pediatric PAH patients and reported that the incidence of side effects of tadalafil was significantly lower in children in comparison to adults. They also reported that there was improvement in WHO functional class, decline in mPAP and survival rates at 1 and 2 year were 98.3 % and 93.7%, respectively (24). In our study a total of 7 patients (3 iPAH and 4 ES), were given tadalafil.…”
Section: Discussionsupporting
confidence: 65%
“…Yamazaki et al investigated the efficacy of tadalafil in pediatric PAH patients and reported that the incidence of side effects of tadalafil was significantly lower in children in comparison to adults. They also reported that there was improvement in WHO functional class, decline in mPAP and survival rates at 1 and 2 year were 98.3 % and 93.7%, respectively (24). In our study a total of 7 patients (3 iPAH and 4 ES), were given tadalafil.…”
Section: Discussionsupporting
confidence: 65%
“…Among 391 patients included in the safety analysis, the overall incidence rate of ADRs was 16.6%. Regarding effectiveness, the incidence of WHO functional class improvement at 3 months, 1 year, and 2 years after the initiation of tadalafil and last observation in pediatric patients were 16.5%, 19.7%, and 16.3%, respectively (42).…”
Section: Phosphodiesterase 5 Inhibitorsmentioning
confidence: 93%
“…Japanese post-marketing surveillance data was used to assess safety and effectiveness of tadalafil in patients <18 years (42). Among 391 patients included in the safety analysis, the overall incidence rate of ADRs was 16.6%.…”
Section: Phosphodiesterase 5 Inhibitorsmentioning
confidence: 99%
“…There are no randomized controlled trials studying tadalafil in the pediatric PAH population. However, three studies suggest that tadalafil 1 mg/kg (maximum 40 mg) daily is well‐tolerated and demonstrates efficacy in the pediatric PAH population 26–28 . Compared with sildenafil, tadalafil has a longer half‐life and is administered once daily, making it an attractive agent from a compliance standpoint.…”
Section: Pde5‐inhibitorsmentioning
confidence: 99%